Rights of patients required in a public service ombudsman - Maristela Santini Martins; Priscila Becher Goese; Marta Martins Barrionovo; Maria Cristina Komatsu Braga Massarollo (Rev Rene)
Objective: analyzing the rights of patients required in a public service ombudsmen. Methods: an exploratory, descriptivestudy of documentary research. 109 complaint forms coming from the basic network were analyzed, related to 12 BasicHealth Units located within the Southern Health Technical Supervision. Results: grouped into four categories of requiredrights: access to goods and services (62.4%) being, access to specialized exams (28.7%), access to consultations (16.6%),referral to a specialist (5.7%), referral for urgent/emergency cases (1.3%), monitoring through home visits (7.6%),guaranteed medications (2.5%). Quality of health services (36.9%) divided into: decent, considerate and respectful care(26.8%), guidance/clarification (9.6%), and public disclosure of government programs (0.6%) and adequate infrastructure(0.6%). Conclusion: the rights that patients required are related to access, quality, treatment and adequate infrastructure.